Analyze Variable TPACK (Technological, Pedagogical, and Content Knowledge) in Digital Learning: A Review - Menrisal (RADINKA JAYA UTAMA PUBLISHER, 2023)
In particular, the Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), and Technological Content Knowledge (TCK) variables are the focus of this study, which attempts to ascertain the relationship between them. and Knowledge of Technological Pedagogical Content (TPACK). The Preferred Reporting Items for A review method used in this study. The study's findings that the TK on TCK, TK on TPK, TK on TPACK, and TPK on TPACK have a positive influence on each other. However, two relationships—the CK on TPACK and the PK variable on TPACK—do not have a positive or significant effect. Ten of the twelve hypothesized variables have a positive influence, while the other two have no discernible effect. It is intended that the research would improve teachers' TPACK skills, particularly in pedagogical and subject knowledge. Tags: Guru skills, TPACK, SmartPls